2019
DOI: 10.1111/cei.13368
|View full text |Cite
|
Sign up to set email alerts
|

Multi-component meningococcal serogroup B (MenB)-4C vaccine induces effective opsonophagocytic killing in children with a complement deficiency

Abstract: Vaccination against meningococcal serogroup B is recommended for patients with a complement deficiency; however, although immunogenicity in this patient group has been shown, efficacy has not yet been established. In this study, we collected serum from children with a complement deficiency in the alternative pathway or in late terminal pathway before and after vaccination with multi-component meningococcal serogroup B (MenB)-4C. MenB-4C is a multi-component, protein-based vaccine against MenB consisting of fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 21 publications
2
15
0
Order By: Relevance
“…Increased whole blood killing of N. meningitidis serogroup Z was observed after MenB-4C vaccination, which is consistent with previous results with N. meningitidis serogroup B. 8 This indicates that there is cross protection that results in increased clearance of the bacterium (Fig. 1E).…”
Section: Assessment Of Cross Reactivitysupporting
confidence: 92%
“…Increased whole blood killing of N. meningitidis serogroup Z was observed after MenB-4C vaccination, which is consistent with previous results with N. meningitidis serogroup B. 8 This indicates that there is cross protection that results in increased clearance of the bacterium (Fig. 1E).…”
Section: Assessment Of Cross Reactivitysupporting
confidence: 92%
“…To address this, we compared two physiologic opsonophagocytosis assays adapted from recently published methods. A hirudin-anticoagulated whole blood assay ( 49 ) was directly compared to an assay based on cells from EDTA-anticoagulated blood, where plasma was removed, cells were washed and supplemented with active serum ( 50 ). The two assays yielded highly comparable results, with both assays demonstrating the relative importance of antibodies and of AP and CP activation for opsonophagocytic killing of pneumococci.…”
Section: Discussionmentioning
confidence: 99%
“…Focusing on isolated cell types, however, reduces the complexity found within whole blood and affects the biological properties of the investigated cell types ( 48 ). Recently, more physiological methods to study complement-mediated opsonophagocytosis of bacteria have been reported that circumvent these limitations ( 49 , 50 ). Hirudin-anticoagulated whole blood – by irreversible direct thrombin inhibition ( 51 ) – can be directly deployed for opsonophagocytosis assays after venous puncture.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since SBA relies exclusively on complement-mediated killing, studies in children and adults with primary terminal complement deficiencies found no serum bactericidal activity against MenB. However, complement-dependent opsonophagocytic killing was still detectable in these individuals, suggesting that they might still be protected following vaccination [38,42]. Measurement of this immune mechanism in this immunocompromised cohort may also be relevant to vaccines against other bacterial pathogens.…”
Section: Opa For Evaluating (New) Bacterial Vaccinesmentioning
confidence: 95%